Hydrothermally induced nanostructured TiO2 coatings - with special reference to biologic events of peri-implant tissue integration - Areid, Nagat (fi=Turun yliopisto|en=University of Turku|, 2021)
Soft tissue integration between the oral implant and the surrounding tissue is considered crucial for implant success. Various surface modifications have been used to obtain bioactive TiO2 coatings on the implant surface to improve osseointegration, bioactivity, and antibacterial properties. Among these methods, the hydrothermal (HT) coating technique has recently gained attention to produce anatase crystalline TiO2 coating for improved bioactivity and enhanced osteoconductivity. However, little is known about HT induced TiO2 coatings effect on the peri-implant soft tissue attachment. The objectives of this series of experimental studies were to develop new HT treatment based TiO2 coatings for titanium implants, which promotes wound healing and enhances soft tissue attachment. Another aim was to investigate the effect of UV light treatment on the bioactivity and antibacterial properties of HT induced TiO2 coatings. Hydrothermal induced TiO2 coatings were prepared by mixing titanium dioxide, purified water and tetramethylammonium hydroxide at 150 ± 10 ºC for 48 hours. The HT coatings were characterized using X-ray photoelectron spectroscopy and scanning electron microscope. The surface wettability was determined using contact angle measurements. Blood clotting ability, plasma protein adsorption, platelet adhesion, and activation, were evaluated. Human gingival fibroblast adhesion and proliferation were studied in a cell culture environment. The effect of UV light on the surface wettability, blood coagulation, and cellular response was investigated on coated and non-coated substrates. A novel tissue culture model using pig mandibular block, including alveolar bone and gingival tissues, was used to evaluate the tissue attachment on coated and non-coated titanium implants. Early biofilm formation on the coated and non¬coated titanium substrates was examined in vivo. The effect of UV light treatment on the biofilm formation was also studied. The HT treated titanium surfaces were entirely covered with coating crystals consisting of nearly spherical TiO2 nanoparticles. Higher carbon contents were observed on non-UV treated surfaces compared to UV treated surfaces, and carbon content was noticed to reduce with increasing UV exposure time. TiO2 coated substrates accelerated blood clotting and improved platelet responses compared with non-coated substrates. Coated substrates showed higher surface free energy and better wettability than non-coated ones. UV treatment enhanced the wettability and improved blood clotting of all examined surfaces. Although no differences in protein adsorption was observed. Fibroblast cell adhesion strength was significantly higher on coated substrates. Histological analysis of pig tissue explants showed epithelial, connective, and bone tissue attachment to both coated and non-coated implant surfaces. The peri-implant epithelium appeared to be in close contact with the coated surfaces. Immunohistochemical staining showed CK14 positivity in the basal cell layer of stratified gingival epithelium. TiO2 coating does not enhance salivary microbial adhesion and initial biofilm formation in vivo. The UV treatment provided titanium surfaces with antibacterial properties and showed a trend towards less biofilm formation than non-UV treated surfaces. It can be concluded that HT derived TiO2 coatings enhance biological events related to wound healing and soft tissue integration on the titanium alloy surface. The UV light treatment improved wettability, thrombogenicity and provided the titanium surfaces with antibacterial properties.

Hydrotermaalisesti indusoidut nanorakenteiset TiO2 pinnoitteet–tutkimuksia peri-implanttikudosten kiinnittymiseen liittyvistä biologisista tapahtumista. Pehmytkudosten kiinnittyminen hammasimplantin pinnalle on tärkeää implanttihoidon onnistumiselle. Erilaisten pintakäsittelyiden avulla implantteihin on pyritty tuottamaan bioaktiivisia TiO2 pinnoitteita parantamaan osseointegraatiota, bioaktiivisuutta ja antimikrobisia ominaisuuksia. Näistä erityisesti hydrotermaalinen (HT) pinnoitusmenetelmä on herättänyt mielenkiintoa kiteisen anataasimuotoisen TiO2 pinnoitteen teossa paremman bioaktiivisuuden ja osteokonduktiivisuuden saavuttamiseksi. Menetelmän vaikutuksia implanttia ympäröivien pehmytkudosten kiinnittymiseen ei tunneta. Tämän väitöskirjan tutkimusten tavoitteina oli kehittää titaani implantteihin uusi HT menetelmällä valmistettu TiO2 pinnoite, joka edesauttaa haavan paranemista ja parantaa ienkudosten kiinnittymistä. Toisena tavoitteena oli tutkia UV-valo käsittelyn vaikutusta HT menetelmällä tuotettujen TiO2 pinnoitteiden bioaktiivisuuteen ja antimikrobisiin ominaisuuksiin. Hydrotermaaliset TiO2 pinnoitteet valmistettiin sekoittamalla titaanidioksidia, puhdistettua vettä ja tetrametyyliammonium hydroksidia 150 ± 10 ºC 48 tunnin ajan. HT pinnoitteet karakterisoitiin RTG-fotoelektronispektroskopiaa ja pyyhkäisyelektronimikroskopiaa käyttämällä. Pintojen kostumisominai¬suuksia tutkittiin kontaktikulmamittausta käyttäen. Veren reaktioita selvitettiin mittaamalla hyytymistä ja plasmaproteiinien kiinnittymistä sekä tutkimalla verihiutaleiden tarttumista ja morfologiaa. Ihmisen ikenen fibroblastisolujen vaste – kiinnittyminen ja jakautuminen -tutkittiin soluviljelyolosuhteissa. UV-valon vaikutus pinojen kostumiseen, veren hyytymiseen ja solujen käyttäytymiseen tutkittiin pinnoitetuilla ja pinnoittamattomilla näytteillä. Uutta kudosviljelymallia käytettiin tutkittaessa sian alaleuan blokkeihin asetettujen pinnoitettujen ja pinnoittamattomien titaani-implanttien kiinnittymistä luuhun ja implanttia ympäröivään ienkudokseen. Varhaisen biofilmin muodostumista pinnoitettuihin ja pinnoittamattomiin titaaninäytteisiin tutkittiin in vivo olosuhteissa. Lisäksi selvitettiin UV-valo käsittelyn vaikutusta biofilmin muodostumiseen. HT menetelmällä käsitellyt pinnat olivat kokonaan kiteisten lähes pyöreiden TiO2 nanopartikkeleiden peittämät. UV-valolla käsittelemättömillä pinnoilla todettiin suurempi hiilikontaminaatio UV-käsiteltyihin pintoihin verrattuna ja hiilipitoisuuden havaittiin pienenevän UV-käsittelyajan pidentyessä TiO2 pinnoite nopeutti veren hyytymistä ja paransi verihiutaleiden reaktioita pinnoittamattomiin näytteisiin verrattuna. Pinnoitettujen titaaninäytteiden vapaa pintaenergia sekä pintojen kostuminen olivat selvästi pinnoittamattomia paremmat. UV käsittely paransi pintojen kostumista ja nopeutti veren hyytymistä kaikilla pinnoilla. Proteiinin adsorboitumisessa ei kuitenkaan havaittu eroja. Fibroblastit kiinnittyivät selvästi voimakkaammin pinnoitetuille näytteille. Sian kudosnäytteillä tehty tutkimus osoitti epiteeli-, side¬ja luukudoksen kiinnittyvän hyvin sekä pinnoitettuihin että pinnoittamattomiin implantteihin. Peri¬implantti epiteeli oli läheisessä kontaktissa pinnoitettuihin pintoihin. Immunohistokemiallinen värjäys osoitti CK14 positiivisuutta stratifioidun ienepiteelin basaalisolukerroksessa. TiO2 pinnoite ei lisää syljen mikrobien kiinnittymistä tai varhaisen biofilmin muodostumista in vivo. UV-valo käsittely muutti pintoja antimikrobisiksi ja vähemmän biofilmin muodostusta suosivaksi käsittelemättömiin pintoihin verrattuna. Tulokset osoittivat, että HT menetelmällä valmistetut TiO2 pinnoitteet tehostavat haavan paranemisen biologisia tapahtumia ja pehmytkudosten kiinnittymistä titaanin pinnalle. UV-valo käsittely lisää pintojen kostumista, trombogeenisyyttä ja muuttaa pintojen ominaisuuksia antimikrobisiksi.